2018
DOI: 10.21273/hortsci12964-18
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Trait Priorities of the Blueberry Industry in the United States and Canada

Abstract: Developing new blueberry cultivars requires plant breeders to be aware of current and emerging needs throughout the supply chain, from producer to consumer. Because breeding perennial crop plants (such as blueberry) is time- and resource-intensive, understanding and targeting priority traits is critical to enhancing the efficiency of breeding programs. This study assesses blueberry industry breeding priorities for fruit and plant quality traits based on a survey conducted at commodity group meetings ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 31 publications
(44 reference statements)
0
50
0
Order By: Relevance
“…Thus, determining whether SHB is capable of acidifying its rhizosphere independently of N form might be a first step in breeding blueberries that tolerate neutral or higher pH soils. This trait has been identified as a priority for blueberry breeders in the United States and Canada (Gallardo et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, determining whether SHB is capable of acidifying its rhizosphere independently of N form might be a first step in breeding blueberries that tolerate neutral or higher pH soils. This trait has been identified as a priority for blueberry breeders in the United States and Canada (Gallardo et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…A recent survey of blueberry growers in the United States and Canada indicated that stem blight is among the more important blueberry diseases (Gallardo et al, 2018). Accelerating the evaluation process and increasing the accuracy of selection are necessary for introgression of disease resistance genes into widely adapted blueberry cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…To quantify the importance of traits and industry related variables across regions, we analyzed the data using an ordered probit model given that the dependent variable, the ranking of traits, was discrete and ordinal as described by Gallardo et al (2018). Each breeding trait described in the previous section was included in the econometric model as a variable, and was assigned a number according to each respondent's ranking.…”
Section: Discussionmentioning
confidence: 99%
“…Traits not identified by the respondent as being among the most or the least important in the trait cluster fruit quality were considered middle choices and were assigned the median value, in this case 3. This method has been used in previous research to elicit the relative level of importance of product attributes (Davis and Gillespie, 2004;Gallardo et al, 2018;Greene and Hensher, 2008;Yue et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation